Patterns of discrimination based on sexual orientation in Africa: is there a Lusophone exception? - Garrido, R. (African Human Rights Yearbook, 2019)
This article analyses the legal developments in African Lusophone countries regarding sexual orientation and the legal-political choices made by these states about the regulation of consensual same-sex acts between adults. Under colonial rule, all Portuguese territories in Africa had sodomy laws in place. After independence, in 1975, the new countries reformed their penal codes and repealed sodomy laws, most of them shifting from criminalisation to protection of sexual orientation. Compared to the situation in other parts of the African continent, where violence against homosexuals is generalised, colonial criminalisation of consensual same-sex acts is still in force or where new laws that further criminalise sexual orientation have been adopted or are under consideration, Lusophone Africans demonstrate higher levels of acceptance of the homosexuality of their fellow citizens, and there is less hostility from the state. Starting with an analysis on international developments in human rights law and jurisprudence regarding prohibition of discrimination based on sexual orientation, this article focusses on the five African Lusophone countries, analysing the legal reforms adopted, the role played by legislative initiatives and the dialogue of states with supranational human rights mechanisms to better protect their citizens from discrimination of any kind. African Lusophone countries took a distinctive legal-political approach, not only by repealing sodomy laws but also by granting other forms of protection based on sexual orientation. They also provide a distinctive narrative regarding homosexuality in Africa, against its usual portrayal as a Western and un-African phenomenon, demonstrating a continent deeply divided on this particular human rights issue.